Mobile Multimedia Based-Microlearning and Assessment on Calculus to Improve Student Mathematical Understanding - Yendra, Novi; Ade Fricticarani; Beni Junedi; Hidayat, Amat (Universitas Pendidikan Ganesha, 2024)
Learning implemented in a blended form has not been maximized in presenting the material, the presentation of the material is extensive and extensive so that the material is difficult to understand, in the assessment aspect of online learning, it has not been able to measure individual abilities, and it is difficult to measure these abilities. This study aims to develop valid and practical multimedia mobile-based microlearning and assessment in calculus lectures. The type of research used is Research and Development (R&D) with a 4D development model (Define, Design, Development, Dissemination). The research instrument used is a validity sheet in the form of a questionnaire validated by material experts, media experts and language experts. The questionnaire was used to measure the practicality of student responses to the products developed on 40 students taking calculus lectures. The data analysis technique used is the percentage of validity and practicality of the products developed. The results of the study indicate that the development of multimedia mobile-based-microlearning and assessment developed based on material experts, media experts, and language experts obtained valid criteria and based on student responses, the multimedia mobile-based microlearning and assessment developed met practical criteria. It can be concluded that the development of multimedia mobile based microlearning and assessment meets the valid and practical criteria for use in calculus lectures and can facilitate the improvement of students' mathematical understanding.